Relationships Between Balance and Cognition in Patients With Subjective Cognitive Impairment, Mild Cognitive Impairment, and Alzheimer Disease. Issue 8 (1st August 2014) - Tangen, Gro Gujord; Engedal, Knut; Bergland, Astrid; Moger, Tron Anders; Mengshoel, Anne Marit
Abstract : Background: Balance impairments are common in patients with Alzheimer disease (AD), but which aspects of balance are affected, at which stage of cognitive impairment, and their associations with cognitive domains remain unexplored. Objectives: The aims of this study were: (1) to explore differences in balance abilities among patients with subjective cognitive impairment (SCI) or mild cognitive impairment (MCI), mild AD, and moderate AD and (2) to examine the relationship between the various aspects of balance and cognitive domains. Design: This was a cross-sectional study. Methods: Home-dwelling patients with SCI or MCI (n=33), mild AD (n=99), and moderate AD (n=38) participated in this study. The Balance Evaluation Systems Test (BESTest), comprising 6 subscales—"Biomechanical Constraints, " "Stability Limits/Verticality, " "Anticipatory Postural Adjustments, " "Postural Responses, " "Sensory Orientation, " and "Stability in Gait"—was used to assess balance. Cognitive domains were assessed using the following measures: Mini-Mental Status Examination, Word-List Learning Test from the Consortium to Establish a Registry for Alzheimer's Disease (CERAD), Verbal Fluency Test, Clock Drawing Test, and Trail Making Test, parts A and B (TMT-A and TMT-B, respectively). Two-way between-group analyses of variance, adjusted for age, were used to analyze differences among the groups. Multiple linear regression analysis was used to explore the associations between balance and cognition. Results: Differences were found between the groups on all BESTest subscales; the moderate AD group had the worst scores. The TMT-B (measuring executive function) was associated with all of the BESTest subscales after controlling for demographic factors. Limitations: The cross-sectional design hampered interpretation of the development of balance impairments. Conclusions: The study findings indicate that all aspects of balance control deteriorate with increasing severity of cognitive impairment and that executive function plays an important role in balance control. Physical therapists should pay attention to these findings both in clinical practice and in future research.